Water molecules on the liquid superlubricity interfaces achieved by phosphoric acid solution. Issue 3 (10th September 2018) - Gao, Yuan; Ma, Liran; Liang, Yong; Li, Bohong; Luo, Jianbin
Abstract : The superlubricity mechanism of phospholipid molecules on biological surfaces and interfaces has been receiving much attention. Since the superlubricity can be achieved with a phosphoric acid aqueous solution, the interaction of the phosphate group with the water molecule is considered to be the key to bio‐lubrication. However, no direct evidence has been offered to distinctly interpret the underlying mechanism of superlubricity, due to the limitations in the method for the detection of interfacial molecules, especially water molecules on the interface. By using sum‐frequency generation (SFG) vibrational spectroscopy, which is extremely sensitive to interfacial molecules, the authors were able to explore the underlying microscopic mechanism for superlubricity in a phosphoric acid system, which might be related to interfacial water molecules. By trapping the phosphoric acid aqueous solution between silicon nitride and silica surfaces, they discovered that phosphoric acid could exercise a great influence on the ordered structure of interfacial water molecules, contributing to SFG spectral changes in the broad O–H bond stretching region. This work directly revealed the interfacial interaction between water and phosphoric acid molecules in liquid superlubricity interfaces, which could shed new light on the microscopic mechanism of liquid superlubricity.